Upregulation of brain hepcidin in prion diseases: Short title: Hepcidin and brain iron accumulation. Issue 1 (1st January 2021) - Chaudhary, Suman; Ashok, Ajay; Wise, Aaron S.; Rana, Neil A.; McDonald, Dallas; Kritikos, Alexander E.; Kong, Qingzhong; Singh, Neena
ABSTRACT: Accumulation of redox-active iron in human sporadic Creutzfeldt-Jakob disease (sCJD) brain tissue and scrapie-infected mouse brains has been demonstrated previously. Here, we explored whether upregulation of local hepcidin secreted within the brain is the underlying cause of iron accumulation and associated toxicity. Using scrapie-infected mouse brains, we demonstrate transcriptional upregulation of hepcidin relative to controls. As a result, ferroportin (Fpn), the downstream effector of hepcidin and the only known iron export protein was downregulated, and ferritin, an iron storage protein was upregulated, suggesting increased intracellular iron. A similar transcriptional and translational upregulation of hepcidin, and decreased expression of Fpn and an increase in ferritin expression was observed in sCJD brain tissue. Further evaluation in human neuroblastoma cells (M17) exposed to synthetic mini-hepcidin showed downregulation of Fpn, upregulation of ferritin, and an increase in reactive oxygen species (ROS), resulting in cytotoxicity in a dose-dependent manner. Similar effects were noted in primary neurons isolated from mouse brain. As in M17 cells, primary neurons accumulated ferritin and ROS, and showed toxicity at five times lower concentration of mini-hepcidin. These observations suggest that upregulation of brain hepcidin plays a significant role in iron accumulation and associated neurotoxicity in human and animal prion disorders.